Aktivitas Online Public Relations melalui Pengelolaan Media Sosial Instagram @RSU_Harkel - Nurhakim, Muhamad Ariq; Fuad, Ahmad (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This research aims to elucidate the online public relations activities through Instagram management @rsu_harkel conducted by Rumah Sakit Umum Harapan Keluarga using David Armano’s 4C concept consisting of Content, Context, Connectivity, and Continuity aspects. This study employs a descriptive method with a qualitative approach. Researchers use in-depth interviews, passive participation observation, and documentation to address the research questions. The research findings indicate that Rumah Sakit Umum Harapan Keluarga engages in online public relations activities with four stages, namely content determination, context adjustment, interaction stimulation, and planning and evaluation.